The Influence of Peer Interaction and Emotional Intelligence on Student Achievement in Class XI Online Business and Marketing at Budi Agung Medan - Putri Mauliza (Outline Journal of Education, 2023)
This study aims to determine the effect of Peer Interaction and Emotional Intelligence on the Learning Achievement of Class XI Students in Online Business and Marketing at the Budi Agung Private Vocational School in Medan. The population of this study were students of class XI Online Business and Marketing at Budi Agung Medan Private Vocational High School, totaling 54 students. The instrument used in data collection was a questionnaire in the form of a Likert scale. The results of data analysis using multiple linear regression and hypothesis testing and it was concluded that peer interaction and emotional intelligence affect the learning achievement of class XI students of Online Business and Marketing at Budi Agung Medan Private Vocational School. This can be seen from the results of multiple linear analysis obtained by the equation Y = 25.018 + 0.358 (X₁) + 0.382 (X₂) then seen from the significant value between peer interaction that influences learning achievement as indicated by the value of t_count>t_table (2.730>2.007) and significance value (0.009<0.05). Furthermore, it can be seen that emotional intelligence influences learning achievement with t_count>t_table (2.771>2.007) and significance value (0.008<0.05). Simultaneously (F test) is indicated by the value of F_count>F_table (8.820> 3.18) and a significance value (0.001 <0.05). So that the hypothesis can be said to be accepted. Thus it can be concluded that peer interaction and emotional intelligence have a positive and significant effect on the Learning Achievement of Class XI Students of Online Business and Marketing at Budi Agung Medan Private Vocational School.